2022
DOI: 10.1111/jocs.16432
|View full text |Cite
|
Sign up to set email alerts
|

The effect of recipient BMI on waitlist and post‐transplant outcomes after the 2018 heart transplant allocation policy change

Abstract: Objective: The effects of recipient body mass index (BMI) on waitlist strategies, waitlist outcomes, and post-transplant outcomes among adult patients listed for heart transplantation under the updated 2018 allocation system have not been well characterized. Methods:The United Network of Organ Sharing data set between October 2015 and March 2021 was analyzed, and patients were grouped based on recipient BMI and whether listing occurred in the old (pre-October 2018) or new allocation system.Results: Listing str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Candidates may undergo LVAD implantation or bariatric surgery [81] to promote weight loss, although patients rarely achieve weight loss post-LVAD [82] and may experience adverse outcomes from delayed listing. Although candidates with obesity may be listed at a lower status due to higher LVAD use and lower use of IABP and mechanical/inotropic support, under the current 2018 allocation system, patients with BMI > 30 kg/m 2 have experienced improved waitlist times, transplantation rates, and waitlist mortality [83]. The ISHLT also recommends that the donor body weight be no more than 30% (male) or 20% (female) below that of the recipient [84], which reduces the availability of potential hearts to a candidate with elevated BMI.…”
Section: Elevated Body Mass Indexmentioning
confidence: 99%
“…Candidates may undergo LVAD implantation or bariatric surgery [81] to promote weight loss, although patients rarely achieve weight loss post-LVAD [82] and may experience adverse outcomes from delayed listing. Although candidates with obesity may be listed at a lower status due to higher LVAD use and lower use of IABP and mechanical/inotropic support, under the current 2018 allocation system, patients with BMI > 30 kg/m 2 have experienced improved waitlist times, transplantation rates, and waitlist mortality [83]. The ISHLT also recommends that the donor body weight be no more than 30% (male) or 20% (female) below that of the recipient [84], which reduces the availability of potential hearts to a candidate with elevated BMI.…”
Section: Elevated Body Mass Indexmentioning
confidence: 99%
“…3,4 The current allocation system resulted in improved waitlist times and increased transplant rates, including for groups who previously experienced particularly prolonged wait times, such as patients with blood group O 5 and elevated body mass index (BMI). 6 Although the current allocation system has maintained similar posttransplant outcomes compared to the prior system, 7 the risk factors for posttransplant mortality under the current allocation system have not been well characterized. Due to significant changes to waitlist strategies, particularly with greater utilization of mechanical bridging which has been associated with worse posttransplant outcomes in previous risk scores, 8,9 we sought to examine the risk factors for posttransplant outcomes in the current era.…”
mentioning
confidence: 99%
“…In this issue of the Journal of Cardiac Surgery , Patel et al analyzed the United Network of Organ Sharing database to assess the impact of the 2018 organ allocation policy changes on the waitlist and posttransplant outcomes based on patient BMI 1 . Their analysis demonstrated that the previously recognized trends of increasing use of temporary mechanical support and decreasing use of durable mechanical support generally held across BMI groups.…”
mentioning
confidence: 99%